UJI SPF DAN AKTIVITAS ANTIBAKTERI SEDIAAN SUNSCREEN POWDER EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava L.) TERHADAP Propionibacterium acnes - Nurul Halimah Amimi; Lina Rahmawati Rizkuloh; Susanti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Every human being has different skin problems. Skin problems caused by sun exposure and acne-causing bacteria can be overcome by using a sunscreen powder that contains anti-acne. Natural ingredients that can overcome these problems are guava leaves (Psidium guajava L.) because they contain flavonoid compounds that can absorb ultraviolet light and have antibacterial activity. This study aims to determine the ability of guava leaves as a sunscreen by determining the value of SPF (Sun Protection Factor) using a UV-Vis spectrophotometer and as an anti-acne by calculating the inhibition of Propionibacterium acnes bacteria using the well diffusion method. The preparation formulation uses a variation in the concentration of guava leaf extract of 2.5%, 5%, and 7.5%. The results showed that guava leaf extract can be formulated into a sunscreen powder that meets the requirements. Based on the data obtained, the SPF value and inhibition zone diameter increased according to the high concentration of guava leaf extract used. All three formulas have an SPF value in the maximum protection category. Formula 3 (7.5%) has the highest SPF value of 15.00. The results of bacterial inhibition zone activity in formulas 1 (2.5%) and 2 (5%) were included in the strong category, while formula 3 (7.5%) had an inhibition of 21.33 mm, which was included in the very strong category.